Perception and practices of teenagers on coastal resource conservation in Miag-ao, Iloilo. - Tabi, Faith A.
This is a study on Perception and Practices of Teenagers on Coastal Resource Conservation in seven selected barangays in Miag-ao. The study aimed to know the perception of teen-agers in coastal communities on costal resource conservation and to describe and explain their practices related to conservation and management of their coastal resources. Both secondary and primary data were used in this study. Primary data were gathered from interviews with the Key Informant and from the teenagers. Secondary data were obtained from on-line sources, books, and journals in the library. Data was analyzed using descriptive statistics. The result of the study showed that teenagers were aware of the lawss and issues concerning conservation of caostal resources and its importance. Respondents defined and perceived coastal resource conservation as saving and maintaining the abundance of coastal resources in order to provide the food and livelihood needs of the people. They believed that the above mention can be atained through protecting the endangered fishery resources such as corals from destruction by using passive fishing gears, proper and wise use of the resources. based on the results the research further recommends that studies should be conducted in other castal communities taking into consideration other factors such as government and non-fovernment initiatives and the level of participation of youth in these initiatives. The researcher also recommended that Miag-ao should have a specific program for the youth such as including this sector in information dissemination campaign committee on environment.